GENEALOGI TAFSIR AYAT HAJI: Studi Pemikiran Tafsir Masdar Farid Mas’udi - Kurdi Kurdi; Ahmad Zaeni; Abdul Muiz; Siti Hajar; Nurkhaeriyah Nurkhaeriyah; M. Khozinul Huda; Mukhlis Mukhlis (Al-Mufassir: Jurnal Ilmu Alquran, Tafsir dan Studi Islam, 2024)
The preferred choice of understanding the Hajj verses is in a very limited time, even though these verses show flexibility in the time of implementation, namely in 3 months, namely Shawwal, Dzulqa'dah and Dzulhijjah. According to Masdar, expanding the time for the Hajj must be implemented by Muslims today by returning to the understanding of the verses regarding the flexibility of time as understood from the verses, however, Masdar's understanding is considered rare and difficult to accept by the majority of Islamic scholars with evidence to date that the application of the Hajj verses still indicates limited pilgrimage time. At this point it is necessary to trace the sources, methods and contributions of Masdar Farid Mas'udi's thoughts in understanding the Hajj verses. To handle this research problem, researchers used contextual interpretation theory, using a socio-historical approach. The results of the research are 1) the ideas of Masdar Farid Mas'udi (Surat al-Baqarah verse 197) which refers to the classical mufassir era, to be precise, four schools of thought are true, namely the months of Shawwal, Dzulqa'dah and Dzulhijjah. It's just that this month is understood as an extension of the ihram time, while the Hajj is still carried out on 8-13 Dzulhijjah; 2) the interpretation method used by Masdar F.M. Hermeneutical contextual in nature